¿Qué es y cómo se mide el Turismo Cultural? Un estudio longitudinal con series temporales para el caso Español - Mallor, Elodie; González-Gallarza Granizo, Martina; Fayos Gardó, Teresa (PASOS Revista de Turismo y Patrimonio Cultural, 2013)
Cultural tourism has become a challenge for many destinations because it is less sensitive to seasonality and to tourism fashion streams. It is a way of revitalizing interior areas, preserving heritage sites and enhancing employment rates. However, conceptualizing and measuring cultural tourism is not an easy task. In this work, first we offer a conceptual framework of what cultural tourism is, as an interface between experience and authenticity: we then present a review of types of cultural tourism and cultural tourists. Second, after presenting how difficult measuring cultural tourism can be, we present our empirical approach: a longitudinal study on secondary data of several cultural dimensions provided by Spanish public sources. The results obtained by means of linear regressions aim to clarify the impact of cultural tourism in tourism spending.